Influence of ICT on public transport use and behaviour in Seoul - Sungwon Lee; Gyeng Chul Kim; Seung Kook Wu; Jieun Oh (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper explores the impact that advances in Information and Communication Technology (ICT) have on the behaviour of transport users and their mode choice habits in Seoul. It discusses the stated preference survey conducted in Seoul and the analysis carried out using the discrete choice modelling approach to understand the sensitivity of the demand for private and public transport uses on time, cost and availability of ICT.
Keywords: 330; Öffentlicher Nahverkehr; Informationstechnik; Mobilkommunikation; Verkehrsverhalten; Transportzeit; Seoul; Südkorea